Motor representations in the intact hemisphere of the rat are reduced after repetitive training of the impaired forelimb - Barbay, Scott (2012)
BACKGROUND: During recovery from a unilateral cortical stroke, spared cortical motor areas in the contralateral (intact) cerebral cortex are recruited. Pre-clinical studies have demonstrated that compensation with the less-impaired limb may have a detrimental inhibitory effect on the intact cortical hemisphere and could impede recovery of the more-impaired limb. However, evidence from detailed neurophysiological mapping studies in animal models is lacking. OBJECTIVES: The present study examines neurophysiological changes in the intact hemisphere of the rat following a unilateral ischemic infarct to cortical forelimb motor areas. METHODS: Eight rats were trained for two weeks on a reach and retrieval task prior to an ischemic infarct induced by the vasoconstrictor, endothelin-1 injected into the cortical grey matter encompassing the two forelimb motor representations, the caudal forelimb area (CFA) and the rostral forelimb area (RFA). Animals were randomly assigned to an Infarct/Training group (n=4) or an Infarct/No Training group (i.e., spontaneous recovery, n=4). After a five-week post-infarct period, motor areas of the intact hemisphere (CFA and RFA) were characterized using intracortical microstimulation techniques. The resulting maps of evoked movements were compared to maps derived from CFA and RFA in normal rats (Normal, n=5; Normal/Training, n=4). RESULTS: Compared with the Normal/No Training group, CFA representations were significantly smaller in the Infarct/Training group but not in the Infarct/No Training group. No significant differences were found in RFA. CONCLUSIONS: Repetitive training of the more-impaired forelimb during the post-infarct recovery period reduces the size of motor representations in the intact hemisphere.